Low perceived control over health is associated with lower treatment uptake in a high mortality population of Bolivian forager-farmers. (March 2018) - Alami, Sarah; Stieglitz, Jonathan; Kaplan, Hillard; Gurven, Michael
Abstract: Indigenous people worldwide suffer from higher rates of morbidity and mortality than neighboring populations. In addition to having limited access to public health infrastructure, indigenous people may also have priorities and health perceptions that deter them from seeking adequate modern healthcare. Here we propose that living in a harsh and unpredictable environment reduces motivation to pursue deliberate, costly action to improve health outcomes. We assess whether variation in Health Locus of Control (HLC), a psychological construct designed to capture self-efficacy with respect to health, explains variation in treatment uptake behavior among Tsimane Amerindians (N = 690; age range: 40–89 years; 55.8% female; data collection: 2008–2012), a high mortality and morbidity indigenous population in the Bolivian Amazon, Beni Department. Comparisons with two industrialized populations in Japan (Miyagi prefecture; e0 = 76.6 years) and the United Kingdom (Caerphilly county borough; e0 = 81.2 years) confirm that Tsimane (e0 = 54.1 years) have a more externalized HLC. Multilevel level models were used to investigate whether HLC predicts treatment uptake, and mediates the relationship between modernization and treatment uptake. External HLC scores were predictive of treatment outcomes: Powerful others scores were positively associated with probability of receiving modern treatment (adjusted odds ratio [OR] = 1.33), while Chance scores were negatively associated with probability of receiving modern treatment (adjusted OR = 0.76). We found no effects, however, of Internal HLC or educational capital on treatment uptake. Overall, our findings indicate that health-related decision-making is influenced more by a psychological orientation affecting self-efficacy, shaped in part by perceptions of environmental unpredictability and harshness, than by limited knowledge, education or other indicators of modernization. Highlights: HLC is a strong predictor of treatment uptake for high morbidity-mortality Tsimane. External but not Internal HLC associates with healthcare treatment uptake. An externalized locus may be a rational response to environmental unpredictability. Education is positively associated with HLC but does not predict treatment uptake. Modern treatment is complementary to traditional options, not a substitute.